Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Review: 111

Answer

(y + 7)(y - 3)

Work Step by Step

$(y + 2)^{2}$ - 25 = $y^{2}$ + 4y + 4 - 25 = $y^{2}$ + 4y - 21 = (y + 7)(y - 3) Check by multiplying factors with FOIL: y(y) + y(-3) + 7(y) + 7(-3) = $y^{2}$ - 3y + 7y - 21 = $y^{2}$ + 4y - 21
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.